Legislation, Repugnancy and the Disallowance of Colonial Laws: The Legal Structure of Empire and Lloyd’s case (1844) - Ward, Damen (Victoria University of Wellington Law Review, 2010)
The imperial government had the ability to disallow New Zealand colonial ordinances that were "repugnant to the laws of England". "Repugnancy" did not operate as a clear legal criterion; the British government could take into account a range of political factors. Instructions to governors were sometimes used to avoid potential legal questions about the impact of disallowance. Henry Samuel Chapman’s judgment in Lloyd’s case (1844) provides a basis for exploring the legal, administrative and political practices surrounding the disallowance of colonial laws. Judges’ and officials’ views on how disallowance took effect show the interaction between political authority, political communication, and legal institutions in a Crown Colony. Lloyd, and Chapman’s extra-judicial writing about repugnancy, help illustrate changing colonial views of the imperial constitution across the mid-nineteenth century. The case therefore shows how New Zealand legal history can contribute to a wider historiography of empire.